The Effect Of Leverage, Profitability, And Dividend Policy On Firm Value - Saputri, Diah Ragil; Bahri, Syaiful (CV. Inara, 2021)
This study aims to examine the effect of leverage, profitability, and dividend policy variables on firm value in property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This type of research is causal associative. The research population is 64 companies. The sample was determined by purposive sampling technique as many as 11 companies. Data analysis used multiple linear regression analysis. The test results show that leverage as proxied by debt to equity ratio (DER) has no significant effect on firm value, profitability proxied by return on equity (ROE) has a significant effect on firm value, and dividend policy proxied by dividend payout ratio (DPR) has no significant effect on the value of the company. Investors pay more attention to the company's ability to earn profits and its management.